Financial transaction taxes and the informational efficiency of financial markets: A structural estimation - Marco Cipriani; Antonio Guarino; Andreas Uthemann (Federal Reserve Bank of New York, 2021)
We develop a new methodology to estimate the impact of a financial transaction tax (FTT) on financial market outcomes. In our sequential trading model, there are price-elastic noise and informed traders. We estimate the model through maximum likelihood for a sample of sixty New York Stock Exchange (NYSE) stocks in 2017. We quantify the effect of introducing an FTT given the parameter estimates. An FTT increases the proportion of informed trading, improves information aggregation, but lowers trading volume and welfare. For some less-liquid stocks, however, an FTT blocks private information aggregation.
Keywords: G14; D82; C13; 330; financial transaction tax; market microstructure; structural estimation